Identification of Ectoparasites in Pearl Catfish (Clarias gariepinus) One and Three Months Ages in Makalele Cultivation Tuban District, Tuban Regency - Galuh Swa Ardhya; Azizatun Nimah; Hani Plumeriastuti; Setiawan Koesdarto; Budiarto Budiarto (Journal of Parasite Science (JoPS), 2022)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â  The purpose of this study was to identify ectoparasites that attack pearl catfish and the incidence of ectoparasite infestation in 100 samples of pearl catfish aged one and three months. This research was carried out from January to March 2021 in Makalele's cultivation, Tuban's District, Tuban's Regency. The method used in this research is skin scraping and gill installation. Data analysis using Chi-Square Test with SPSS version 24.0 for windows. The results showed that there were 3 types of ectoparasites found, Trichodina nobilis, Trichodina pediculus, Chilodonella sp., Dactylogyrus sp. and the highest incidence of ectoparasites occurred in young fish compared to old fish with a percentage of 35% and 25%, respectively, and based on the chi-square test there was no significant difference (pï¸â‰¥0.05).Â Keywords: Clarias gariepinus, infestation level, ectoparasites.